Analisis Kemampuan Berpikir Kritis Mahasiswa Pendidikan Fisika Tentang Teknologi Pemanfaatan Sinar Ultraviolet Pada Bidang Kesehatan - Azurulia Maurilla Syifa; Sudarti S (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the critical thinking ability of physics education students in understanding the use of ultraviolet light in the health sector. The research method used in this research is using a qualitative descriptive method. The research subjects used are physics education students in semester 5 , totaling 42 people . The data collection technique was using a reasoned questionnaire written test. The critical thinking indicators that are measured are identifying, providing further explanation, concluding, and determining strategies and tactics. From the research data then analyzed to determine the presentation. From the results of the data analysis, it can be concluded that the critical thinking ability of physics education students is still around 32.6%, and is still fairly poor in solving problems regarding technology for the use of ultraviolet light in the health sector.